IMPLEMENTING THE MAKE A MATCH LEARNING MODEL TO IMPROVE VOCABULARY MASTERY - Nurul Hikmah; Candraning Prihatini; Zohri Hamdani (STKIP PGRI Lubuklinggau, 2025)
This study “aimed to improve students’ vocabulary mastery through the implementation of the Make a Match learning model at Pontrenmu Darul Arqom Natar. The research was conducted as a Classroom Action Research (CAR) in two cycles, involving 10 eighth-grade students. Each cycle consisted of planning, action, observation, and reflection. Data were collected using observation, documentation, and vocabulary tests, and were analyzed both quantitatively and qualitatively. The findings revealed significant improvements in students’ vocabulary achievement. The average score increased from 71.6 in Cycle I with 40% mastery to 83.3 in Cycle II with 90% mastery. Qualitative observations also showed that students became more enthusiastic, confident, and actively engaged in the learning process. In conclusion, the Make a Match model proved effective not only in enhancing vocabulary mastery but also in creating an interactive and enjoyable classroom environment. Therefore, this method is recommended as an alternative strategy for teaching vocabulary.”